Lactarius deliciosus isolate UEZB1 internal transcribed spacer 1, partial sequence; 5.8S ribosomal RNA gene and internal transcribed spacer 2, complete sequence; and 28S ribosomal RNA gene, partial sequence - Santos-Silva, Celeste (2013)
LOCUS JQ066791 439 bp DNA linear PLN 20-MAR-2012 DEFINITION Lactarius deliciosus isolate UEZB1 internal transcribed spacer 1, partial sequence; 5.8S ribosomal RNA gene and internal transcribed spacer 2, complete sequence; and 28S ribosomal RNA gene, partial sequence. ACCESSION JQ066791 VERSION JQ066791.1 GI:380467948 KEYWORDS . SOURCE Lactarius deliciosus ORGANISM Lactarius deliciosus Eukaryota; Fungi; Dikarya; Basidiomycota; Agaricomycotina; Agaricomycetes; Russulales; Russulaceae; Lactarius.